2004
DOI: 10.1002/marc.200400103
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Monolayer Formed by a Rhenium Complex Containing Hyperbranched Polymer

Abstract: Summary: The synthesis of a hyperbranched polymer containing a rhenium bipyridine complex is reported. The polymer was synthesized from a monomer that contains two chlorotricarbonyl rhenium(I) bipyridine moieties and a stilbazole ligand, and the polymer was formed by the coordination reaction in one single step. Gel permeation chromatography results showed that the resulting polymer had a strong interaction with the column packing material, which was reduced when the eluent was added with an electrolyte. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…[26] It was synthesized by a one-step reaction in which the monomer units were linked together by coordination between the stilbazole ligand and the rhenium center. GPC analysis showed two peaks in the chromatogram, and the high-molecular-weight peak was attributed to the interaction between the charged polymer and the column materials.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[26] It was synthesized by a one-step reaction in which the monomer units were linked together by coordination between the stilbazole ligand and the rhenium center. GPC analysis showed two peaks in the chromatogram, and the high-molecular-weight peak was attributed to the interaction between the charged polymer and the column materials.…”
Section: Resultsmentioning
confidence: 99%
“…This value agrees with our previous atomic force microscopic (AFM) studies in which the size of the polymer molecules deposited on a silicon wafer was found to be 25-30 nm. [26] Such a large molecular size may be due to the repulsion between charges on different branches in the polymer molecule, which lead to a more extended conformation. In general, r g decreases with the concentration of salt in polyelectrolyte solution due to the screening of charges by the excess counterions added, [34,35] and the presence of salt may also suppress the aggregation of polymer molecules.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, N,N-dimethylformamide and N-methylpyroridone containing KPF6 or NH4PF6 have been used in the GPC analysis of polymers with cationic ruthenium(II) and rhenium(I) complexes. 8,9 However, these solvents are not suitable for preparative chromatography, because their high boiling points make it difficult to remove the solvent. Polar solvents with stable and relatively low boiling points, such as methanol and acetonitrile, should be suitable for more general applications of SEC to multinuclear metal complexes, but they cannot be used as eluents for hydrocarbon-based GPC columns.…”
Section: Introductionmentioning
confidence: 99%